Effect of Brahmi (Bacopa Monnieri) in the Treatment of Alzheimer's Disease from Ayurvedic Perspective - A Systematic Review (AYUSHDHARA, 2023)
Objectives: Treatment of Alzheimer’s disease is the worldwide problem as it is having major impact on the memory. Ayurveda science describes Brahmi (Bacopa Monnieri) as memory enhancing drug which can improve the memory power in the Alzheimer’s disease. Data Sources: Classical textbooks and published research studies were searched in the context of use of Brahmi (Bacopa Monnieri) in the Alzheimer’s disease. Online search engines namely J gate, Google scholar, PubMed, DHARA online and AYUSH research portal were used for data mining of published research works. Review Methods: References and studies including the effect of Brahmi (Bacopa Monnieri) in the treatment of Alzheimer’s disease were reviewed and reported according to the PRISMA guidelines. We include randomized controlled trials with mild cognitive impairment in Alzheimer’s disease which involves Bacopa Monnieri, its extract or its active ingredients. Results and Discussion: 5 studies found eligible for the search. Two studies used extracts of Bacopa Monnieri extracts while three studies used other drugs in combination with the Bacopa Monnieri extract. The cognitive subscale scores of the Alzheimer’s disease Assessment scale found in one study, mini mental state examination scores were found in three studies. All the studies found a significant difference in statistics. Hence, Brahmi (Bacopa Monnieri) may find to be effective in Alzheimer’s disease and its equivalent disease in Ayurveda. Conclusion: The evidence obtained from the present systematic review is of very low certainty. The evidence from 5 trials suggests that there is a very little difference between Bacopa Monnieri and a placebo or donepezil in the treatment of Alzheimer disease or mild cognitive impairment which needs to find in further future studies No major safety issues were reported in the trials included in this review.